Improvement of knowledge in NLP based on AI for students and teachers in the fashion department - Af'idah, Dwi Intan; Handayani, Sharfina Febbi; Hidayattullah, Muhammad Fikri; Imamah, Putri Ajeng (Journal of Community Service and Empowerment, 2024)
The fashion department at SMK Negeri 1 Warureja faces significant challenges in understanding and applying Artificial Intelligence (AI)-based Natural Language Processing (NLP) among its students and teachers. Despite the potential benefits of NLP technology for the fashion industry, the limited knowledge and skills concerning NLP tools at SMK Negeri 1 Warureja impede effective utilization. This Community Service Program (CSP) is strategically designed to address these gaps by providing targeted training on NLP tools such as ChatGPT, Chatbot, and Brand24.com within the fashion context. This CSP activity applies the technique of training an initial evaluation through a pre-test assessed participants' baseline understanding prior to the training. During the practical tutorial phase, participants received hands-on training with NLP tools, including practical guidance to ensure real-world application of these concepts. Evaluation results indicated a significant improvement in participants' understanding and skills. The post-test average of 80.47 points showed a significant improvement of 32.19 points over the pre-test average of 48.28 points.